High incidence of acute coronary occlusion in patients without protocol positive ST segment elevation referred to an open access primary angioplasty programme. Issue 1053 (30th March 2013) - Apps, Andrew; Malhotra, Aseem; Tarkin, Jason; Smith, Robert; Kabir, Tito; Lane, Rebecca; Mason, Mark; Ali, Omar; Rogers, Paula; Banya, Winston; Whitbread, Mark; Ilsley, Charles; et al.
Abstract : Background: Primary percutaneous coronary intervention (PPCI) programmes vary in admission criteria from open referral to acceptance of electrocardiogram (ECG) protocol positive patients only. Rigid criteria may result in some patients with acutely occluded coronary arteries not receiving timely reperfusion therapy. Objective: To compare the prevalence of acute coronary occlusion and, in these cases, single time point biomarker estimates of myocardial infarct size between patients presenting with protocol positive ECG changes and those presenting with less diagnostic changes in the primary angioplasty cohort of an open access PPCI programme. Methods: We retrospectively performed a single centre cross sectional analysis of consecutive patients receiving PPCI between January and August 2008. Cases were categorised according to presenting ECG—group A: protocol positive (ST segment elevation/left bundle branch block/posterior ST elevation myocardial infarction), group B: ST segment depression or T-wave inversion, or group C: minor ECG changes. Clinical characteristics, coronary flow grades and 12 h postprocedure troponin-I levels were reviewed. Results: During the study period there were 513 activations of the PPCI service, of which 390 underwent immediate angiography and 308 underwent PPCI. Of those undergoing PPCI, 221 (72%) were in group A, 41 (13%) in group B and 46 (15%) in group C. Prevalence of coronary occlusion was 75% in group A compared with 73% in group B and 63% in group C. Median 12 h postintervention troponin-I (25th–75th percentile) for those with coronary occlusion was significantly higher in group A patients; 28.9 μg/l (13.2–58.5) versus 18.1 μg/l (6.7–32.4) for group B (p=0.03); and 15.5 μg/l (3.8–22.0) for group C (p<0.001), suggesting greater infarct size in group A. Conclusions: A number of patients referred to an open access PPCI programme have protocol negative ECGs but myocardial infarction and acute coronary artery occlusion amenable to angioplasty.